2004
DOI: 10.1111/j.1440-0960.2004.00032.x
|View full text |Cite
|
Sign up to set email alerts
|

Inverted follicular keratosis simulating malignant melanoma

Abstract: A 93-year-old woman was noted to have a single pigmented lesion on the posterior aspect of her neck. Clinical examination revealed a 12 x 8-mm flat lesion, with an irregular border and variegated pigmentation. Dermatoscopic examination revealed a lesion with multiple colours, featureless areas and black dots, suggestive of malignant melanoma. With a presumed clinical diagnosis of malignant melanoma, an elliptical excision was performed, with a 1-cm margin. However, histological examination revealed the unexpec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…There is only 1 case reported as a rare pigmented IFK mimicking, clinically and dermoscopically, a melanoma, with variegated pigmentation, presence of featureless areas and black dots on dermoscopy [3]. However, it was a very rare presentation form of IFK because, as mentioned previously, the most frequent clinical picture of an IFK is a nonpigmented scaly or keratotic papule.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is only 1 case reported as a rare pigmented IFK mimicking, clinically and dermoscopically, a melanoma, with variegated pigmentation, presence of featureless areas and black dots on dermoscopy [3]. However, it was a very rare presentation form of IFK because, as mentioned previously, the most frequent clinical picture of an IFK is a nonpigmented scaly or keratotic papule.…”
Section: Discussionmentioning
confidence: 99%
“…Usually the clinical appearance is difficult to differentiate from other keratinizing proliferations such as seborrheic keratosis (SK) or viral wart (VW), and malignant tumors such as squamous cell carcinoma (SCC) and basal cell carcinoma (BCC). This is why diagnosis is generally made on the basis of histology rather than clinical examination [3]. …”
Section: Introductionmentioning
confidence: 99%
“…Following surgical excision, no invasive growth or metastasis have been reported in the literature. [ 11 ] In our patient, topical 5% imiquimod cream was started, and near complete regression was detected after two months of treatment. A review of the literature revealed no other similar case that was successfully treated with 5% imiquimod cream.…”
Section: Discussionmentioning
confidence: 79%
“…[ 2 ] Thus, it may mimic many cutaneous conditions including seborrheic keratosis, melanoacanthoma, squamous cell carcinoma, basal cell carcinoma, and melanoma. [ 2 3 ] Not surprisingly, the diagnosis of IFK is often missed clinically and reveals itself on histopathology. Differentiating IFK from irritated seborrhoeic keratosis (SK) is difficult.…”
mentioning
confidence: 99%